An Economical Mathematics Model - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2018)
In the frame of the project NTP-NFTÖ-17-C-159, one of my main tasks is to present the possible applications of teaching mathematics in high schools and in higher education. Beside this, I would like to illustrate that, in many cases, how useful and, in certain cases, indispensable the use of mathemathical softwares is during the solution of a complex problem.